Energy Balance in Critically Ill Children With Severe Sepsis Using Indirect Calorimetry: A Prospective Cohort Study. Issue 6 (June 2019) - Ismail, Javed; Bansal, Arun; Jayashree, Muralidharan; Nallasamy, Karthi; Attri, Savita V.
ABSTRACT: Objectives: Energy needs in critically ill children are dynamic and variable. Data on energy balance in children with severe sepsis using indirect calorimetry (IC) is lacking. Thus, we planned to study the energy needs and balance of this cohort. Methods: Prospective observational study conducted in ventilated children aged 5 to 12 years, admitted in pediatric intensive care unit with severe sepsis from May 2016 to June 2017. Measured resting energy expenditure (mREE) was measured with IC (Quark RMR, COSMED) till 7 days or pediatric intensive care unit discharge. Predicted energy expenditure (pREE) was estimated using Schofield, Harris and Benedict, and FAO/WHO/UNU equations. Primary outcome was to study the daily energy balance. Secondary outcome was to determine nitrogen balance and agreement of mREE with pREE. Results: Forty children (24 boys) with median age of 7 (5.2, 10) years were enrolled. All received enteral nutrition; 35 (87.5%) received inotropic support. Median ventilation-free days were 19 days and 4 children died (10%). A total of 176 IC measurements were obtained with an average of 4 per patient. The mean mREE was 51 ± 17 kcal/kg and mean respiratory quotient was 0.77 ± 0.07. There was persistent negative energy balance from days 1 to 7 and negative nitrogen balance from days 1 to 5. There was poor agreement of pREE with mREE using Bland Altman plots. None of severity of illness scores (PRISM III, daily Sequential Organ Function Assessment, daily Vasoactive Inotropic Score) showed correlation with mREE. Conclusions: Persistent negative energy and nitrogen balance exist during acute phase of severe sepsis. Predictive equations are inaccurate compared with IC as the criterion standard. Abstract : Supplemental Digital Content is available in the text